Biosecurity measures and effects on health performance and antibiotic use in semi-intensive broiler farms in Uganda - Ayebare, Dreck; Mbatidde, Irene; Kemunto, Naomi P.; Muloi, Dishon M.; Ibayi, Eugine L.; Nielsen, S.S.; Ndoboli, Dickson; Roesel, Kristina; Tenhagen, B.-A.; Moodley, Arshnee (Elsevier, 2025)
Background: Effective biosecurity measures prevent the spread of pathogens, thereby reducing the need for antibiotic use on livestock farms. However, quantitative data on these practices and health outcomes in semi-intensive broiler farms in low-income settings is limited. A longitudinal study in Wakiso, Uganda, aimed to evaluate biosecurity practices, health performance, and antibiotic use in such farms.